Euphorbia hypericifolia L. (Euphorbiaceae), an Overlooked Invasive Alien Species from Telangana State, India - Arigela, Ravi Kiran; Krishna, Peddi Hari; Sudhakar Reddy, C. (Indian Forester, 2023)
No Abstract.